(untitled) (International Journal of Physiotherapy, 2017)
Background: Postural drainage is used exclusively or in combination with other airway clearance techniques in the management of chronic pulmonary diseases. Postural drainage therapy helps to prevent accumulation of secretions in patients who are at high risk for pulmonary complications. It also helps to remove accumulated secretions from the lungs.The role of body positioning on lung function and the clinical implications of postural drainage has been identified in a variety of settings including intensive care units. There is dearth in literature on effects on postural drainage on vital parameters. Thus the objective of the study was to measure the vital parameters at different postural drainage positions in healthy asymptomatic adults. Methods: Twenty healthy subjects participated in the study. The instruments used in the current study included a Pulse oximeter, Sphygmomanometer, Stethoscope, Postural drainage table.The outcome measures of interest were heart rate, respiratoryrate, oxygen saturation, blood pressure and Borg’s scale of rate of perceived exertion. The changes in the vital signs were recorded at different head down titling position of 0°, 15° & 30° in both supine and prone lying positions Results: Statistical significant difference was found for Systolic Blood Pressure in prone lying at different degrees of tilt (p=0.001) and Diastolic Blood Pressure in prone lying (p=0.000). Conclusion: Postural drainage positioning should be given with caution and under proper monitoring as there is a risk of change in the blood pressure even in asymptomatic elderly population. The monitoring of vital signs should be done during the therapy to decrease the risk of complications.